Distinct temporal actions of different types of unfolded protein responses during aging. Issue 7 (21st December 2020) - Sheng, Yi; Yang, Guang; Markovich, Zachary; Han, Sung Min; Xiao, Rui
Abstract: Proteotoxic stress is a common challenge for all organisms. Among various mechanisms involved in defending such stress, the evolutionarily conserved unfolded protein responses (UPRs) play a key role across species. Interestingly, UPRs can occur in different subcellular compartments including the endoplasmic reticulum (UPR ER ), mitochondria (UPR MITO ), and cytoplasm (UPR CYTO ) through distinct mechanisms. While previous studies have shown that the UPRs are intuitively linked to organismal aging, a systematic assay on the temporal regulation of different type of UPRs during aging is still lacking. Here, using Caenorhabditis elegans ( C. elegans ) as the model system, we found that the endogenous UPRs (UPR ER, UPR MITO, and UPR CYTO ) elevate with age, but their inducibility exhibits an age‐dependent decline. Moreover, we revealed that the temporal requirements to induce different types of UPRs are distinct. Namely, while the UPR MITO can only be induced during the larval stage, the UPR ER can be induced until early adulthood and the inducibility of UPR CYTO is well maintained until mid‐late stage of life. Furthermore, we showed that different tissues may exhibit distinct temporal profiles of UPR inducibility during aging. Collectively, our findings demonstrate that UPRs of different subcellular compartments may have distinct temporal mechanisms during aging. Abstract : A normalized, permutated radar chart is used to compare the endogenous unfolded protein responses (UPRs) (a) and induced UPRs (b) at different ages. Overall, the endogenous UPRs elevate during aging, while different types of induced UPRs exhibit distinct age‐related decline rates.